Moringa Leaf-Based Gastronomic Tourism in Taro Village, Gianyar, Bali - Putu Eka Wirawan; Ni Luh Supartini; I Made Sudiana (International Journal of Social Science and Business, 2022)
The COVID-19 pandemic which has destroyed all tourism in Bali itself, has had implications for the emergence of various businesses to survive, various efforts were made. After the pandemic ended, the rate of development of the number of tourist attractions in Bali increased. That became a challenge for villages that already had existing tourist destinations. Gastronomic tourism is another alternative for tourists to enjoy processed foods that are considered healthy, so that it becomes a potential for diversifying a tourist destination to be sustainable. This study aims to look at tourism potential and analyze the model of developing gastronomic tourism in Taro Tegallalang Village, Gianyar Bali. This study uses a qualitative method with a critical descriptive approach, so that most of the data obtained from qualitative data are mostly sourced from observations, literature studies and in-depth interviews. This study concludes that the potential for gastronomic tourism there is quite high, by taking the following steps: involving local farmers in providing Moringa plantations, requiring strong support and role of local government, maximum involvement of Pokdarwis, synergy with tourism businesses, mapping potential candidates. tourists, and making various tourist routes so that they are not boring.